Advaita as a global international relations theory - Shahi, Deepshikha (Rethinking Asia and international relations, 2019)
Advaita in international relations : a philosophical restoration -- Reality, appearance and unreality of international politics : an Advaitic review -- Temporality and spatiality of international relations : an Advaitic reconfiguration -- The Advaitic theory of international relations : reconciling dualism and monism in the pursuit of the "global"